2011
DOI: 10.17763/haer.81.2.92315ww157656k3u
|View full text |Cite
|
Sign up to set email alerts
|

Pipelines and Pathways: Women of Color in Undergraduate STEM Majors and the College Experiences That Contribute to Persistence

Abstract: Supporting undergraduate achievement in science, technology, engineering, and mathematics (STEM) disciplines is paramount to ensuring our nation's continued scientific and technological advancement. In this quantitative study, Lorelle Espinosa examines the effect of precollege characteristics, college experiences, and institutional setting on the persistence of undergraduate women of color in STEM majors and also investigates how this pathway might differ for women of color in comparison to their White peers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
418
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 456 publications
(436 citation statements)
references
References 11 publications
18
418
0
Order By: Relevance
“…Within the higher education literature, sense of belonging is a known predictor of success in college (e.g., Freeman et al 2007;Pittman and Richmond 2008;Strayhorn 2012), especially within STEM disciplines (Espinosa 2011;Johnson 2012). Sense of belonging refers to the extent to which individuals feel like they belong or fit in a given environment.…”
Section: Purposementioning
confidence: 99%
“…Within the higher education literature, sense of belonging is a known predictor of success in college (e.g., Freeman et al 2007;Pittman and Richmond 2008;Strayhorn 2012), especially within STEM disciplines (Espinosa 2011;Johnson 2012). Sense of belonging refers to the extent to which individuals feel like they belong or fit in a given environment.…”
Section: Purposementioning
confidence: 99%
“…Additionally, a wealth of research (e.g., Espinosa, 2009;Hurtado et al, 2011;Perna et al, 2009) has begun to narrow in on the unique experiences of underrepresented minority students in STEM fields at the baccalaureate level. A particularly important contribution to this initiative lies in Ong, Wright, Espinosa, and Orfield's (Ong et al, 2012) review of forty years of research related to women of color's experiences in baccalaureate-and graduate-level STEM fields; this work incorporates attention to the temporal component, similar to our present work, and also sought to identify important shifts in the literature.…”
Section: Meta-narrative 1: Individual Background Characteristicsmentioning
confidence: 99%
“…Currently, less than half of the three million students entering higher education to pursue a STEM field persist to earn a STEM degree 3 . The drop-out rate from STEM is even more prominent in minorities and women 4 ; however, participating in undergraduate research and developing a strong peer network has been shown to increase persistence 5,6,7,8,9 . While we seek to engage students in research experiences to encourage persistence, in the University of Illinois at Urbana Champaign's (UIUC) Bioengineering Department attrition is not a major problem, but by engaging students in focused research experiences we seek to increase persistence in scientific research after graduation, whether that be in industry, academia, or clinical settings 7,10,11 .…”
Section: Implementing a Challenge-inspired Undergraduate Experience Imentioning
confidence: 99%